Interactions of domain antibody (dAbκ11) with Mycobacterium tuberculosis Ac2SGL in complex with CD1b. (January 2019) - Law, Cheh Tat; Camacho, Frank; Garcia-Alles, Luis F.; Gilleron, Martine; Sarmiento, Maria E.; Norazmi, Mohd Nor; Acosta, Armando; Choong, Yee Siew
Abstract: Tuberculosis (TB) is the main cause of mortality among all infectious diseases. The presentation of lipids by CD1b molecules and the interactions of the CD1b-lipid complexes with the immune receptors are important for the understanding of the immune response to Mycobacterium tuberculosis (Mtb), and to develop TB control methods. A specific domain antibody (dAbk11) recognizing the complex of CD1b with Mtb sulphoglycolipid (Ac2 SGL) had been previously developed. In order to study the interactions of dAbk11 with Ac2 SGL:CD1b, the conformation of Ac2 SGL within CD1b was first modelled. The orientation of dAbκ11 with Ac2 SGL:CD1b was then predicted by a docking experiment and the complex was sampled using molecular dynamics simulation. Data showed that dAbκ11 Tyr32 OH plays a decisive role in interacting with Ac2 SGL alkyl tail HO17 . The binding free energy calculation showed that Ac2 SGL establish strong hydrophobic interactions with dAbκ11. The model also predicted a higher affinity for the natural sulfoglycolipid (Ac2 SGL) than the synthetic analogue (SGL12), which was supported by the ELISA data. These results shed light on the likely mechanism of interactions between Ac2 SGL:CD1b and dAbκ11, thus making possible to envision the strategies for dAbκ11 optimization for possible future applications.